2020
DOI: 10.3390/ijms21072445
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis Reveals the Potential Mechanism of Abortion in Tobacco sua-Cytoplasmic Male Sterility

Abstract: sua-CMS (cytoplasmic male sterility) is the only male sterile system in tobacco breeding, but the mechanism of abortion is unclear. Cytological characteristics show that abortion in the sua-CMS line msZY occurs before the differentiation of sporogenous cells. In this study, a comparative transcriptomic analysis was conducted on flower buds at the abortion stage of msZY and its male fertile control ZY. A total of 462 differentially expressed genes were identified in msZY and ZY, which were enriched via protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 76 publications
(90 reference statements)
0
2
0
Order By: Relevance
“…1 c). KEGG enrichment analysis revealed that the targets of DEmiRNAs were significantly enriched in several pathways that may be related to anther development, including ‘plant hormone signal transduction’, which plays an important regulatory role in plant anther development 31 , ‘endocytosis’, which is essential for the development of male reproductive organs in Arabidopsis 32 , ‘plant–pathogen interaction’, which plays a dominate role in recessive genic male sterility of cabbage 33 , ‘protein processing in the endoplasmic reticulum’, and ‘oxidative phosphorylation’, which were also significantly enriched in the comparative transcriptome analysis of tobacco sua -cytoplasmic male sterility, indicating that they may be involved in anther development 34 (Fig. 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…1 c). KEGG enrichment analysis revealed that the targets of DEmiRNAs were significantly enriched in several pathways that may be related to anther development, including ‘plant hormone signal transduction’, which plays an important regulatory role in plant anther development 31 , ‘endocytosis’, which is essential for the development of male reproductive organs in Arabidopsis 32 , ‘plant–pathogen interaction’, which plays a dominate role in recessive genic male sterility of cabbage 33 , ‘protein processing in the endoplasmic reticulum’, and ‘oxidative phosphorylation’, which were also significantly enriched in the comparative transcriptome analysis of tobacco sua -cytoplasmic male sterility, indicating that they may be involved in anther development 34 (Fig. 1 d).…”
Section: Resultsmentioning
confidence: 99%
“…Tobacco sua -CMS is the only CMS system in tobacco breeding. A comparative transcriptomic analysis showed that genes involved in the ER stress pathway, heat shock protein family, F 1 F 0 -ATPase, and differentiation of stages are down-regulated in sua -CMS, while genes in the programmed cell death (PCD) pathway are significantly up-regulated, indicating that PCD and defects in ATP synthesis are crucial to the pollen abortion of sua -CMS [ 36 ]. A proteomic analysis of Shaan2A-CMS in B. napus showed that the differentially expressed proteins were related mainly to carbohydrate metabolism, energy metabolism, and genetic information processing pathways [ 37 ].…”
Section: Introductionmentioning
confidence: 99%